(untitled) (Communication & Society, 2005)
This article examines the adaptation of the media library belonging to a digital media. The first part starts by defining what a digital media library is; secondly, shows its fundamental processes at work; the final part describes both typical functions which have been revived, and new functions that have appeared, that answer the needs of online journalists and of online journalism.